Vertical Gardens in Goiânia: Potentials and Limitations as a Strategy for Climate Mitigation and Thermal Comfort - Aires, Luana Xavier Monteiro da Silva; Milagre , Carolina Vivas da Costa; Mendonça, Fernanda Antônia Fontes; Cruz, Layara Alves (Technical and Scientific Journal Green Cities, 2025)
Objective –The article aims to analyze the implementation of vertical gardens, based on case studies of buildings in Goiânia, and discuss their impacts as a climate mitigation strategy, thermal comfort for buildings and aesthetic solution. Methodology – The methodology is based on a bibliographic review, analysis of reports and case studies of buildings in Goiânia. Originality/Relevance – The article is part of the discussion of nature-based solutions, raising questions about the implementation of vertical gardens on building facades, analyzing their structure and technical solution. Results – The results indicate that, in the established context, vertical gardens have been implemented with erroneous structures that distort their character, leading them to be understood as merely aesthetic, combined with a sustainability discourse distorted by the real estate market and losing their potential as a climate mitigation solution. Theoretical/Methodological Contributions – Based on the research, it is highlighted the need to discuss practical solutions in the face of densification and rapid urban expansion, specifically in Goiânia, which is experiencing accelerated real estate investment, and the importance of confronting the distorted sustainability discourse that has been used by current interventions. Social and Environmental Contributions –The research is moving toward an exploration of vertical garden technologies with cost-reduction strategies that can reach other social classes, as well as other nature-based techniques, in order to contribute to discussions on practical climate mitigation infrastructures for the city.